Alternatif Pembenahan Muatan Materi Rancangan Peraturan Perundang-Undangan Melalui Policy Screening Tools - Hanif Hardianto; Megafury Apriandhini; Nina Farliana (Fakultas Hukum, Universitas Warmadewa, 2026)
Indonesia is a state based on the rule of law, and one of the characteristics of such a state is that all policies issued by the government must be grounded in applicable legal norms. The hierarchy of legislation in Indonesia does not consist solely of laws (undang-undang); at the lowest level, there are still district/municipal regulations (peraturan daerah kabupaten/kota). Indonesia is experiencing a crisis in the legislative process, which has led to several laws and regulations receiving criticism and even rejection from the public. This situation is alarming, especially if the legislative process continues in this manner in the future. Law, which should function as social control, has instead become a source of new problems and is ineffective because it fails to accommodate the interests of society. This study is qualitative research using a sociological legal approach, focusing on understanding the procedures for forming laws and regulations using the Policy Screening Tools in the Secretariat General of the Provincial DPRD in Bali and Aceh. Policy Screening Tools serve as a policy analysis instrument that can act as a parameter to determine whether a draft regional regulation is suitable or unsuitable to be enacted. Not all draft laws and regional regulations undergo screening—only those draft laws and regulations that face contention among the legislature, the executive, and the public are subjected to the screening process.